New forms of interception and contragestation: a biomedical review - Romano, Lucio (Studia Bioethica, 2009)
The instruction Dignitas Personae, between the various and current bioethics issues that takes into account, reserves adequate consideration to “New forms of interception and contragestation” . Defines the classification according to their mechanisms of action (“[…] methods are interceptive if they interfere with the embryo before implantation and contragestative if they cause the elimination of the embryo once implanted”) ; represents and justifies the immorality of abortion (“Therefore, the use of means of interception and contragestation fall within the sin of abortion and are gravely immoral”) and intention of abortion (“[…] anyone who seeks to prevent the implantation of an embryo which may possibly have been conceived and who therefore either requests or prescribes such a pharmaceutical, generally intends abortion”) . “As is known, abortion is the deliberate and direct killing, by whatever means it is carried out, of a human being in the initial phase of his or her existence, extending from conception to birth” . Preliminary remark the recognition of the dignity of person to every human being, from conception (“The dignity of a person must be recognized in every human being from conception to natural death”) .The aim of this article is a biomedical review of the new forms of interception and contragestation (only hormonal methods), with arguments supported by specialized scientific literature. Moreover, another purpose is to show how there is always a strong link between contraception and abortion .